Study on the Tribological Behavior of Wear and Friction Coefficient on AISI M35 High-Speed Steel with and without DLC Coating - Paulo Sérgio Martins; José Rubens Gonçalves Carneiro; Elhadji Cheikh Talibouya Ba; Vitor Ferreira Vieira; Diego Boaventura Amaral; Nilson Cristino da Cruz (Materials Research, 2021)
Abstract To improve the wear resistance of cutting tools made of high-speed steel, the Diamond-Like Carbon (DLC) coating appears as a promising alternative. There are several methods to assess wear, however, it is a challenge for manufacturing engineering to work with thin films, due to the uncertainty in the boundary of the substrate and the coating. Based on this concern, this study proposed the evaluation of the tribological behavior of the DLC coating deposited on AISI M35 steel, seeking to predict its behavior in machining conditions based on characterizations, nano-indentation, micro-abrasion and ball-on-disc test. Results showed that the DLC coating produced for this study consists mainly of sp2 hybridizations. The results of the nano-indentation showed that DLC coating may have a better wear resistance when compared to high-speed steel, and the nano-hardness and Young's modulus do not necessarily obey a positive correlation. Compared to high-speed steel, DLC provided reductions of 71% and 69% without micro-abrasive wear and without friction coefficient during sliding, respectively.